2022
DOI: 10.1136/bmjopen-2021-051721
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear relationship between basal serum albumin concentration and cardiac arrest in critically ill patients with end-stage renal disease: a cross-sectional study

Abstract: ObjectivesThe aim of our study was to investigate the association between serum albumin concentration and the risk of cardiac arrest in critically ill patients with end-stage renal disease in the intensive care unit (ICU).DesignThis was a secondary analysis.SettingThe Phillip electronic-ICU collaborative database from 2014 to 2015.ParticipantsThis study included 4990 critically ill patients diagnosed with end-stage renal disease.Primary and secondary outcome measuresThe exposure of interest was serum albumin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…On another note, the association between higher levels of albumin and decreased risk of cardiac arrest in dialysis patients has been previously described [20]. Albumin levels in this population are typically low due to reduced albumin synthesis in the setting of a chronic inflammatory state, albumin loss in the urine and protein loss from dialysis itself (20).…”
Section: Rapa Et Al Emphasized the Role Of Inflammation And Oxidative...mentioning
confidence: 89%
See 1 more Smart Citation
“…On another note, the association between higher levels of albumin and decreased risk of cardiac arrest in dialysis patients has been previously described [20]. Albumin levels in this population are typically low due to reduced albumin synthesis in the setting of a chronic inflammatory state, albumin loss in the urine and protein loss from dialysis itself (20).…”
Section: Rapa Et Al Emphasized the Role Of Inflammation And Oxidative...mentioning
confidence: 89%
“…Albumin levels in this population are typically low due to reduced albumin synthesis in the setting of a chronic inflammatory state, albumin loss in the urine and protein loss from dialysis itself (20). Albumin contributes to uremic toxin removal and has anticoagulant/antithrombotic effects so lower levels of this marker is unsurprisingly associated with higher risk of cardiac arrest [20].…”
Section: Rapa Et Al Emphasized the Role Of Inflammation And Oxidative...mentioning
confidence: 99%
“…Albumin is synthesized by the liver and has important physiological functions, such as anti-inflammatory and antioxidant activities, scavenging free radicals, and maintaining plasma osmolality. When the body is infected or hit, the consumption of albumin increases, and studies have shown that lower albumin levels are associated with increased mortality in patients with various diseases [ 8 , 9 , 10 ]. In addition, multiple studies have shown that elevated LDH and decreased albumin levels are associated with poor outcomes in CA patients [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%